“Ali Baba and the 40 Metaverses”: Ethical paradigms related to the metaverse in business contexts - Coelho, M. R. S. S.; Ferreira, F. A. F.; Ferreira, N. C. M. Q. F.; Ferreira, J. J. M.; Santos, M. R. (Strategic Change, 2025)
The metaverse is rapidly emerging as a key area of interest in business circles, promising an immersive experience for all users through virtual worlds. Within these computer-generated realms, users can create avatars to represent themselves and engage with other avatars and virtual environments. The title “Ali Baba and the 40 Metaverses” underscores the transformative potential of this innovation, which is often perceived as a magical technology. “Open sesame” was the magical phrase spoken to enter the cave in “Ali Baba and the 40 Thieves”, so too is the gateway into the enchanted realm of the metaverse—where the imagination reigns supreme—technologies such as virtual or augmented reality. However, the alluring prospect of the metaverse is associated with ethical issues that must be considered carefully, as they could significantly influence its acceptance and integration into societies and business settings. Using the 6-3-5 method | brainwriting and stepladder technique, this study develops a process-oriented analysis system to help companies identify and address ethical challenges related to metaverse technology. The results are based on two sessions with an expert panel, which not only shed light on the ethical paradigms associated with the metaverse but also provide actionable insights for businesses navigating this emerging landscape. To ensure the integrity and reliability of the findings, a consolidation session was conducted with an independent expert to validate the identified paradigms and pinpoint areas needing improvement.